Verbal anglicisms with suffix endings -ova-, -a-, and -irain the Bosnian language – the frequency of use and the knowledge of their meaning - Delić, Haris; Dedović-Atilla, Elma; Džanković, Asmir; Burcu Kapukaya, Mihrimah (ExELL, 2025)
Languages do not operate in isolation; rather, they evolve in continuous contact with other languages. This contact and resultant lexical borrowing can lead to minor or substantial changes in the vocabulary of the recipient language. This quantitative study aims to analyze how borrowing from the English language affects the formation of new verbs in the Bosnian language (verbal Anglicisms) and which suffixes in the Bosnian language (between -ova-, -a-, -ira-) are most often used to form new verbs. Additionally, the aim is to explore the frequency of use and the level of knowledge of the meaning of verbal Anglicisms. The study was conducted on 345 participants, i.e. both male and female high school students from Bosnia Herzegovina. The results indicate that verbal Anglicisms with the suffix -a- are the most often used group of verbal Anglicisms and that this preference is a result of the nature and origin of those Anglicisms (mostly IT-related) and is not related to the linguistic nature of the Bosnian language. Furthermore, it was shown that knowledge of the original form of verbal Anglicisms affects the level of their use, and that level of use of these Anglicisms is influenced by the EL GPA and medium of instruction of the respondents, while gender, grade level, and experience of traveling to English-speaking countries are not significant factors in the extent of usage of these Anglicisms. Further investigation is proposed to broaden the scope of the present research in different settings and among various study groups.